2004
DOI: 10.1042/bj20040218
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of N-acetylneuraminic acid synthase isoenzyme 1 from Campylobacter jejuni

Abstract: Escherichia coli NeuNAc (N-acetylneuraminic acid) synthase catalyses the condensation of PEP (phosphoenolpyruvate) and ManNAc (N-acetylmannosamine) to form NeuNAc and is encoded by the neuB gene. Campylobacter jejuni has three neuB genes, one of which is very similar to the E. coli neuB gene. We have characterized the C. jejuni neuraminic acid synthase with respect to acylamino sugar specificity and stereochemistry of the PEP condensation. We determined the specificity of C. jejuni NeuNAc synthase for N-acetyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
46
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 29 publications
4
46
0
Order By: Relevance
“…The extent of 18 O incorporation at the C-2 position was determined to be 54% by mass spectrometry: 16 O, 85). 31 P NMR spectroscopy was used to determine that the position of the label was at the C-2 position:…”
Section: C-o Versus P-o Bond Cleavage-[2-mentioning
confidence: 99%
See 2 more Smart Citations
“…The extent of 18 O incorporation at the C-2 position was determined to be 54% by mass spectrometry: 16 O, 85). 31 P NMR spectroscopy was used to determine that the position of the label was at the C-2 position:…”
Section: C-o Versus P-o Bond Cleavage-[2-mentioning
confidence: 99%
“…1A). Three genes that show homology to neuB were identified in C. jejuni, where one encoded a sialic acid synthase (neuB1) and the other two genes were thought to encode proteins that modify the flagellin proteins (neuB2 and neuB3) (8,16). NeuB3 shows 35.0% identity to the NeuB from Neisseria meningitidis and was found to be essential for the formation of flagella because an insertional mutation in the gene resulted in aflagellate C. jejuni (8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanistic studies have shown that the reaction proceeds via an anti-elimination of UDP to give the enzyme-bound intermediate 2-acetamidoglucal, followed by the syn-addition of water to give ManNAc (17,19). In a subsequent step the ManNAc is condensed with phosphoenolpyruvate by sialic acid synthase, NeuB, which is homologous to pseudaminic acid synthase and employs a similar reaction mechanism (20,21). Finally, the sialic acid is activated as its CMP form by CMP-sialic acid synthetase, NeuA (22,23).…”
Section: Resultsmentioning
confidence: 99%
“…Since the overall strategy employed in pseudaminic acid biosynthesis (the use of UDP-GlcNAc in ultimately forming a CMP-linked ␣-keto acid) is known to be the same as in sialic acid biosynthesis (24), and since the key synthases are closely related (13,20,21), it seemed possible that the hydrolases may also be homologous. Such an enzyme could catalyze the elimination of UDP from UDP-6-deoxy-AltdiNAc to give a glycal intermediate and then hydrate the double bond of the glycal with overall retention of stereochemistry at C-2 to give the hydrolysis product, 6-deoxy-AltdiNAc.…”
Section: Resultsmentioning
confidence: 99%